Analysis of the relationship between bullying behavior and executive functions in schoolchildren (2021)
Though significant associations are known to exist between Executive Functions (EFs) and aggression, the role of EFs in the context of bullying has rarely been examined in populations of the Caribbean Region of Colombia. This study aims to analyze the relationship between school bullying and the EFs of children and adolescents residing in the Colombian city of Cartagena. The sample was conformed by 181 students from three schools who were evaluated using the abbreviated scale of the School Bullying Questionnaire and the Behavioral Evaluation of Executive Functions BRIEF – 2. The results showed association between various subfactors of the two instruments, which may be clinical indicators of executive dysfunction, mainly in the components of behavioral and emotional regulation, which would be associated with higher levels of school intimidation and symptoms related with bullying. The educational implications of these findings are discussed. © 2021, Universidad Compultense Madrid. All rights reserved.